2009
DOI: 10.11124/jbisrir-2009-181
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Visiting Hour Policies on Pediatric and Adult Patients and their Visitors

Abstract: Educational, supportive and behavioural interventions to improve usage of continuous positive airway pressure machines for adults with obstructive sleep apnoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…16,28 In contrast, many studies reported that liberal visitation policy helps relieve anxiety in the families because they are allowed to spend more time with patients and feel more secured and comfortable. 21,29 33…”
Section: Discussionmentioning
confidence: 99%
“…16,28 In contrast, many studies reported that liberal visitation policy helps relieve anxiety in the families because they are allowed to spend more time with patients and feel more secured and comfortable. 21,29 33…”
Section: Discussionmentioning
confidence: 99%
“…17 Children's visits too are often restricted on the basis of the belief that children pose increased infection risks in patients. 18 Three reports were found on this topic. 18 Three reports were found on this topic.…”
Section: Does Open Visitation Results In Increased Infection Rates?mentioning
confidence: 99%
“…It reassures patients, prevents sensory deprivation and reminds them of the normal out of hospital life (Clark and Harrison, 2001). In a systematic review, Smith et al (2006) reported that visiting decreases the patients' and family members' anxiety and increases their satisfaction. In addition, the presence of visitors in ICU positively affects the patients' outcomes such as sense of well-being and healing process (Obringer et al, 2012).…”
Section: Visiting Outcomesmentioning
confidence: 99%
“…Visiting policies vary widely worldwide (Smith et al, 2006). Restricted visiting policies were established early in the 1800s in general wards for non-paying patients, and were aimed at regularizing the general health care settings; however, such policies have been extensively implemented in all settings -especially ICUs -since the 1960s (Berwick and Kotagal, 2004).…”
Section: Visiting Policiesmentioning
confidence: 99%
See 1 more Smart Citation